Efektivitas Layanan Pos Bantuan Hukum Posbakum Sebagai Upaya Mewujudkan Keadilan Hukum di Pengadilan Negeri Mojokerto Kelas 1A - Firdhauzya, Rahajeng Amatul; Isbandono, Prasetyo (Universitas Negeri Surabaya, 2023)
Indonesia is a country of laws. Everyone has the right to make it happen, but not everyone understands legal issues, especially those who can't afford it. The government has taken steps to overcome this problem, namely by having Posbakum in Court. The purpose of this study was to analyze the effectiveness of the Mojokerto District Court Posbakum services. This type of research is descriptive qualitative. Data collection techniques are carried out by observation, interviews, and documentation. The results of this study indicate that service effectiveness is measured using indicators according to Duncan, namely: (1) Achievement of goals, quite effective and obstacles still found in the time bracket factor (2) Integration, not yet effective because there are obstacles in the process of Posbakum services to the community and related socialization has not yet been carried out widely to villages or sub-districts that are far from the city of Mojokerto. (3) Adaptation, quite effective. Supporting factors in this Posbakum service, there is cooperation with competent parties, there is a budget, there are facilities or facilities to support success. The recommended suggestions are conducting widespread socialization by recording and scheduling remote locations, making videos or information on social media, creating suggestion boxes to criticize services and conducting evaluations. It is hoped that this will increase employee capacity building by participating in training, seminars, technical guidance, workshops related to legal aid services, increasing time discipline and integrating information related to advertising by arranging schedules and hearings and ensuring that the information provided is as needed so you don't feel suffering from waiting. Keywords: Effectiveness, Public services, Posbakum